Catechin: Molecular mechanism of Anti-Cancer Effect: Katekin: Mekanisme Molekular Efek Antikanker - Sari, Liza Meutia (Dentika: Dental Journal, 2019)
Over the recent decade, attention has been focused on the pathologic role of free radicals in a variety of diseases, which are most related to the carcinogenesis process. Carcinogenesis is a multi-step process that is induced primarily by carcinogens leading to the development of cancer. Extensive research in the last few years has revealed that regular consumption of certain fruits and vegetables can reduce the risk of acquiring specific cancers. Catechins are phytochemical compounds found in high concentrations in a variety of plant-based foods and beverages. Studies with cell lines have demonstrated that catechins affect signal transduction pathways, inhibit cell proliferation and induce apoptosis. More mechanistic studies in these areas will help us to understand the inhibitory action of catechin against carcinogenesis and provide background for evaluating the effects of catechin on human carcinogenesis.